Gambaran Sarana Dan Prasarana Penyimpanan Sediaan Farmasi di Logistik Farmasi RSUD M. Natsir Solok Tahun 2025 - Indah Permata Bunda; Erpidawati Erpidawati; Legabina Adzkia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Introduction:This study examines facilities and infrastructure, which are crucial components in supporting the smooth running of hospital processes, particularly in the pharmacy department. Adequate facilities and infrastructure are essential for effective operational activities, although in reality, some healthcare facilities still do not meet established standards. Common problems encountered include limited storage space, inappropriate equipment, and a lack of professional pharmacists. The purpose of this study was to determine the drug storage facilities and infrastructure at M. Natsir Solok Regional General Hospital. The method used was descriptive quantitative, involving 15 logistics officers as respondents. Data were collected through observation, questionnaires, and documentation, then analyzed using SPSS. The results showed that storage facilities maintained appropriate temperatures in 60% of cases and inappropriate temperatures in 40%. Appropriate lighting in 53.3% and inappropriate lighting in 46.7% of cases, and appropriate ventilation in 73.3% and inappropriate ventilation in 26.7%. Regarding infrastructure, 26.7% of stainless steel shelves are in compliance, 60% of pharmacy cabinets, 53.3% of drug refrigerators, and 53.3% of cold storage facilities. In conclusion, the facilities and infrastructure at M. Natsir Solok Regional Hospital largely meet standards, but improvements are needed in ventilation, lighting, and the use of stainless steel shelves